Reesa vespulae - Majka, Christopher G. (Zenodo, 2007)
Reesa vespulae (Milliron, 1939) NOVA SCOTIA: Halifax Co.: Halifax, 7.v.1981, 13.v.1981, 21.v.1981, 15.vi.1981, 1.v.1983, and 24.v.1983, B. Wright, (25), NSMC; Halifax, 14.i.1991, R. Grantham, (2), NSMC; Lake Egmont, 20.vi.1990, E. Parker, NSMC. PRINCE EDWARD ISLAND: Queens Co.: Charlottetown, 4.vii.1986, 1.viii.2000, and summer 1998, M.E.M. Smith, (7), ACPE; Charlottetown, 1.vii.1986, L.S. Thompson, ACPE. Newly recorded in Nova Scotia (Fig. 3). Found in the northern states in the USA (Beal 2003); in Canada recorded across the country from British Columbia and the Northwest Territories east to Newfoundland. A minor pest of insect and plant collections, occasionally found in granaries and dwellings (Bousquet 1990). In natural circumstances it is a scavenger of dead insects and spiders in wasp nests (Beal 1967). Published as part of Majka, Christopher G., 2007, The Derodontidae, Dermestidae, Bostrichidae, and Anobiidae of the Maritime Provinces of Canada (Coleoptera: Bostrichiformia), pp. 1-38 in Zootaxa 1573 (1) on page 16, DOI:10.11646/zootaxa.1573.1.1, http://zenodo.org/record/5096635